"The child is our focus": On couple issues in child oncology treatment. Issue 10 (4th September 2018) - Hooghe, An; Rosenblatt, Paul C.; De Jongh, Sofie; Bakker, Esther; Nijkamp, Marjan; Rober, Peter
Abstract: Objective: This study explored the perspectives of child oncology professionals and parents about the attention professionals should give to the parent couple relationship during treatment of the child. Methods: We employed a qualitative research design, framed within the approach of consensual qualitative research (CQR), gathering data from four focus groups with 20 professionals and from nine in‐depth interviews with 16 parents. Thematic analysis of the focus group and interview data was done with MaxQda software, using two coders and member checks to strengthen confidence in the analysis. Findings: Both professionals and parents talked about an elevated tension in the partner relationship during oncology treatment of the child. However, explicit attention to the partner relationship in this context felt inappropriate to professionals and parents. All emphasized the importance of the professional helpers' openness to conversation and an attuned response to the parental couple relationship. Conclusion: During treatment, the child is the primary focus for parents and professionals. The parents' focus on supporting their child makes talking about their own emotions or about issues in the partner relationship potentially disruptive and unhelpful. Therefore, it is crucial for professionals to support the parents in their parents' role, but with an openness to converse about issues in the partner relationship at the moments when these issues might threaten their focus on the child.